Blind idealism in Ibsen’s Brand - Isaksen, Azadeh Mazloumsaki (Nordlit, 2015)
It has been 112 years since the last play was written by Henrik Ibsen, and he still lives on through his works as a modern dramatist. His plays cannot be set aside; even in our time, they demand to be studied more than ever before. Ibsen has been studied and performed all around the world, especially in Asia, where he speaks to the political and social needs of that part of the world. The combination of current political circumstances, social inequalities, and human rights has given his plays a special urgency in Asia. However, even though Ibsen has seen a particular resurgence in Asia and the Middle East, the terrible events of 22 July 2011 in Oslo and Utøya bear certain traces of Ibsen in his country of birth as well. A false hero, trumpeting himself as a true philosopher in a land in need of rescue, brings only chaos and destruction. Ibsen is considered, from one side, as an idealist whose heroes are divine for rescuing the society from their life-lie. On the other side, he is as a deflator of heroism and a derider of blind idealism. To the former, in his hypothetical society, there is a triangular form at the apex of which a leader stands to lead the masses up from the base. The question is raised here: how do Ibsen’s plays enlighten the debate on the contemporary socio-political issues? By applying historical approach along with contextual methodology, this study answers the above question. The significance of conducting this study on Ibsen’s plays is to know the response of his plays to the current political matters.